2020
DOI: 10.1016/j.marenvres.2019.104795
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the endangered fan mussel Pinna nobilis in the western Mediterranean Sea

Abstract: The present work, which is the first comparative study of the growth of the fan mussel Pinna nobilis in the western Mediterranean, encompasses 12 populations of this species living in different environments in France and Spain. Two hundred nine shells were processed and used to obtain growth records from the posterior adductor muscle scar. Size-at-age data were fitted to the Von Bertalanffy growth model. Considerable variability in growth parameters and age was detected among the populations. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 52 publications
1
48
1
Order By: Relevance
“…This mortality was attributed to illegal fishing in shallow waters, but it is an unlikely hypothesis in our study as the bay of Peyrefite is located in a marine protected area. According to García‐March et al (2007) and García‐March, Hernandis, et al (2020), exposed open sea and shallow habitats, such as the bay of Peyrefite, can be highly stressful for fan mussels as moderate‐to‐high hydrodynamics and waves create disturbances and increase mortality rate. In addition, the area is known to undergo intense air–sea interactions leading to strong winds and large sea states that can have substantial impacts on coastal habitats (Renault et al, 2012), which could be responsible for the lower survival in the bay of Peyrefite.…”
Section: Discussionmentioning
confidence: 99%
“…This mortality was attributed to illegal fishing in shallow waters, but it is an unlikely hypothesis in our study as the bay of Peyrefite is located in a marine protected area. According to García‐March et al (2007) and García‐March, Hernandis, et al (2020), exposed open sea and shallow habitats, such as the bay of Peyrefite, can be highly stressful for fan mussels as moderate‐to‐high hydrodynamics and waves create disturbances and increase mortality rate. In addition, the area is known to undergo intense air–sea interactions leading to strong winds and large sea states that can have substantial impacts on coastal habitats (Renault et al, 2012), which could be responsible for the lower survival in the bay of Peyrefite.…”
Section: Discussionmentioning
confidence: 99%
“…This species is considered one of the most longlived bivalves (Rouanet et al, 2015;García-March et al, 2020a); so far, longevity of P. nobilis has been estimated to 20 years by Butler et al (1993), to 9-12 years by Richardson et al (2004), and over than 20 years by Galinou-Mitsoudi et al (2006) and García-March et al (2011). More recently Rouanet et al (2015) reported two individuals about 45 years old on a population in Port-Cros Island (Provence, France).…”
Section: Pinna Nobilismentioning
confidence: 99%
“…Since then, the situation worsened quickly, with the mass mortality affecting different Mediterranean areas expanding in an eastward direction, and gradually involving Spanish, French, Italian, Croatian, Bosnians and Herzegovinians, Greek and Turkish coasts (Catanese et al, 2018, Katsanevakis et al, 2019, Panarese et al, 2019Cabanellas-Reboredo et al, 2019;Lattos et al, 2020;García-March et al, 2020a;Šarić et al, 2020;Čelebičić et al, 2020). This phenomenon had a great impact on the populations of P. nobilis in a very short timeframe.…”
Section: Dancing On the Edge Of The Abyss: Mass Mortality Runs Over Pinna Nobilismentioning
confidence: 99%
“…Besides nutrient loading, there are several geophysical and biogeochemical variables that influence the survival of P. nobilis . Among them, favorable hydrodynamic conditions are a key factor in the colonization of lagoons, since in these environments P. nobilis rarely experience high water velocities that may prove harmful to them (García‐March et al., 2020). In fact, the survival of the mollusk depends on its ability to anchor through the byssus filaments to sediments such as stones, sand, rhizomes of marine phanerogams, bio‐detrital fragments, and roots.…”
Section: Introductionmentioning
confidence: 99%
“…In such environments the individuals grow fast, due to eutrophic conditions characterized by typically high concentrations of nitrates, ammonium, and phosphorus, that in turn increase the availability of phytoplankton and zooplankton. In lagoons, however, individuals show lower longevity than in open sea conditions (García‐March et al., 2020). These findings confirm a previous study by Alomar et al.…”
Section: Introductionmentioning
confidence: 99%